Indonesia Independensi Wartawan dalam Perspektif Etika Komunikasi Islam - Abdurahman Abdurahman; Septian Liandy; Afta Razhul; Romi Alamsyah (LPPM IAI Pangeran Dharma Kusuma Segeran Indramayu, 2026)
Journalistic independence is a prerequisite for maintaining news credibility and the role of the press as a provider of information to the public. However, editorial work is increasingly influenced by media ownership concentration, political pressure, commercial interests, audience metrics, and algorithm-based information distribution. This article aims to analyze journalistic independence from the perspective of Islamic communication ethics. The study employs a qualitative method using a literature review approach by examining sixteen publications issued between 2020 and 2025, consisting of journal articles, professional guidelines, and press freedom reports. The findings indicate that independence in Islamic communication ethics is not merely understood as institutional freedom from external intervention. It also requires journalists to uphold truth, verification, justice, responsibility, and human dignity. The principles of tabayyun, sidq, amanah, and adl strengthen modern journalistic standards, including accuracy, balance, accountability, and editorial autonomy. This article proposes an operational model that connects personal integrity, editorial protection, source transparency, and public accountability. Such integration is relevant to strengthening Indonesian journalism amid digital disinformation, political polarization, and the economic vulnerability of the media industry.